2010
DOI: 10.1111/j.1365-2966.2009.16093.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying birth places of young isolated neutron stars

Abstract: Young isolated radio-quiet neutron stars are still hot enough to be detectable at X-ray and optical wavelengths due to their thermal emission and can hence probe cooling curves. An identification of their birth sites can constrain their age. For that reason we try to identify the parent associations for four of the so-called Magnificent Seven neutron stars for which proper motion and distance estimates are available. We are tracing back in time each neutron star and possible birth association centre to find cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
127
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 81 publications
(133 citation statements)
references
References 133 publications
(153 reference statements)
5
127
1
Order By: Relevance
“…Because of its space motion ([U, V, W] = [−10.6, −15.4, −7.9]km s −1 ) and its other youth indicators, Zuckerman et al (2001) and Torres et al (2006) proposed that PZ Tel is a member of the β Pic moving group, with an age of 12 +8 −4 Myr. Tetzlaff et al (2010) determined the age of PZ Tel by comparing its luminosity and temperature with several theoretical model isochrones yielding an age of 12.8 ± 2.2 Myr, consistent with the general age estimate for the β Pic moving group. Rebull et al (2008) reported the detection of excess emission in the spectral energy distribution of PZ Tel at 70 μm with MIPS/Spitzer.…”
Section: Introductionmentioning
confidence: 93%
“…Because of its space motion ([U, V, W] = [−10.6, −15.4, −7.9]km s −1 ) and its other youth indicators, Zuckerman et al (2001) and Torres et al (2006) proposed that PZ Tel is a member of the β Pic moving group, with an age of 12 +8 −4 Myr. Tetzlaff et al (2010) determined the age of PZ Tel by comparing its luminosity and temperature with several theoretical model isochrones yielding an age of 12.8 ± 2.2 Myr, consistent with the general age estimate for the β Pic moving group. Rebull et al (2008) reported the detection of excess emission in the spectral energy distribution of PZ Tel at 70 μm with MIPS/Spitzer.…”
Section: Introductionmentioning
confidence: 93%
“…It was suggested that the fields are either "fossil" remnants of the Galactic ISM field, which is amplified during the collapse of a magnetized gas cloud (e.g., Price & Bate 2007), or that they are formed in a dramatic close binary interaction, i.e., in a merger of two stars or a dynamical mass transfer event (e.g., Ferrario et al 2009). Tetzlaff et al (2010) reinvestigated the scenario of a binary SN in Upper Scorpius involving ζ Oph and PSR B1929+10 and concluded that it is very likely that both objects were ejected during the same supernova event. Although in the case of ζ Oph binary interaction is expected, no significant field was detected in this star.…”
Section: Discussionmentioning
confidence: 99%
“…Forbes (2000) provides a distance to the association of 1.9 ± 0.3 kpc, and an average age of 5 ± 1 Myr. Tetzlaff et al (2010) provide a parallax measurement based on Hipparcos stars of 0.63 mas, which correspond to a distance from the Sun of 1.6 kpc and sets an age of the association of 4-5 Myr. On the other hand, the open cluster in the centre of region #2 is NGC 6604, which can be found in the WEBDA catalogue, with a distance of 1.7 kpc, and an age of ∼6 Myr.…”
Section: The Origin Of Ls 5039 and Psr J1825−1446mentioning
confidence: 99%